Exploring the interaction mechanisms of CD46/TREM1 and LC3B/ATG5 in the inflammation-cancer transformation of oral squamous cell carcinoma based on bioinformatics - Xie, Huixian; Xu, Yingjie; Cong, Beibei; Gao, Meihua; Wang, Wanchun (Frontiers in Molecular Biosciences, 2025)
ObjectiveTo investigate the molecular interaction patterns between CD46/TREM1 and LC3B/ATG5 in the development of oral squamous cell carcinoma (OSCC), providing novel targets for elucidating the mechanism of inflammatory-to-cancer progression and for the early diagnosis and treatment of OSCC.MethodsAn oral inflammation-to-cancer progression animal model was established using 4-Nitroquinoline-N-oxide (4-NQO) drinking water and/or lipopolysaccharide (LPS). Clinical oral leukoplakia (OLK), OSCC, and adjacent non-cancerous tissues were collected. Immunohistochemistry assessed CD46, TREM1, LC3B, ATG5 protein expression and PI3K-AKT/TNF pathway alterations in animal and clinical tissues. Enzyme-Linked Immunosorbent Assay (ELISA) measured inflammatory cytokine levels in serum and saliva. High-throughput sequencing analyzed key pathways.ResultsImmunohistochemistry revealed elevated CD46/TREM1 expression and reduced LC3B/ATG5 expression in OSCC tissues (P < 0.05). Serum levels of IL-6, IL-8, and GROα/CXCL1 progressively increased with advancing inflammation-to-cancer progression in rats, whereas salivary expression peaks occurred during the inflammatory phase. In human saliva and serum, TNF-α, IL-8, and IL-6 exhibited an increasing trend among healthy individuals, oral leukoplakia patients, and OSCC patients (P < 0.05). Transcriptome analysis revealed a significant increase in differentially expressed genes during the transformation from OLK to OSCC, predominantly downregulated genes. Among these, Col4a6 and Csf2 genes participated in inflammation-to-cancer progression by regulating the PI3K-Akt and TNF pathways.ConclusionCD46 and TREM1 are highly expressed in OSCC and serve as key initiating factors in the progression from OLK to OSCC. Bioinformatics analysis identified critical candidate genes (Col4a6, Csf2) and pathways (PI3K-Akt, TNF) in inflammation-to-cancer conversion. Activation of the PI3K-AKT-mTOR pathway is associated with inhibited autophagy and malignant progression of OSCC. Additionally, inflammation-to-cancer transition is a core mechanism in the development of OSCC, with the tumor inflammatory microenvironment acting as a “promoter” in the progression from OLK to OSCC. This study provides novel insights into the molecular mechanisms and targeted therapies for OSCC, holding significant theoretical and clinical application value.